Bioinformatics - Lohar, Prakash S (Chennai : MJP, 2009)
Introduction Evolution of Computers Biological Macromolecules Basic Techniques in Bioinformatics Biological Databases Sequence Alignment Multiple Sequence Alignments Computational Gene Prediction Proteomics Genomics Latest Information Covers Basics of Computers Includes Programming Languages Emphasis on Techniques Elaborative Style Many Web Resources and URLs Review Questions Glossary References Index
References 563-574p.and Index 575-580p.